Research of surface properties of water-flour suspensions in the presence of hydrocolloids and protein supplements - Haliasnyi, Ivan; Gavrish, Tetyana; Shanina, Olga (Technology audit and production reserves, 2017)
An important issue of improving the technology of non-yeasted gluten-free bread is the development of measures to improve the structural and mechanical properties of dough and bread. To this end, the use of polysaccharide and protein supplements in the dough phase has been proposed. It is shown that the introduction of hydrocolloids and animal protein concentrates into freeze-free gluten-free dough improves the foaming characteristics by reducing the surface tension in water-flour suspensions. This indicates the formation of more stable systems for improving the porous structure of gluten-free non-yeasted bread. It has been found that the proposed supplements-structure improvers as a whole cause a reduction in shape stability, to the greatest extent – in the case of joint application. Thus, the shape stability index of the control sample (water) is 32, and in the presence of 0.5 % sodium carboxymethyl cellulose with supplements 0.5...1.0 % of Scanpro T95 – 20...21. Under the conditions of the introduction of ScanPro T95 in the amount of 1.5 % there is an increase in the surface tension of the liquid phase of the dough (indicator – 27.4). Explain the decrease in the effectiveness of ScanPro T95 in an amount of 1.5 % can be achieved through possible drag-drop processes with this amount of supplement. Thus, experimental studies have confirmed that the presence of hydrocolloids and animal protein concentrates in the aqueous-flour suspension with flour mix reduces the shape stability index of the drop due to a decrease in its surface tension.